Clinical characteristics of pediatric hospitalizations associated with 2009 pandemic influenza A (H1N1) in Northern Bavaria, Germany - Wieching Anna; Benser Jasmin; Kohlhauser-Vollmuth Christina; Weissbrich Benedikt; Streng Andrea; Liese Johannes G (BMC Research Notes, 2012)
Abstract Background The 2009 pandemic influenza A (H1N1) (PIA) virus infected large parts of the pediatric population with a wide clinical spectrum and an initially unknown complication rate. The aims of our study were to define clinical characteristics and outcome of pandemic influenza A (H1N1) 2009-associated hospitalizations (PIAH) in children <18 years of age. All hospitalized cases of children <18 years of age with laboratory-confirmed pandemic influenza A (H1N1) 2009 in the region of Wuerzburg (Northern Bavaria, Germany) between July 2009 and March 2010 were identified. For these children a medical chart review was performed to determine their clinical characteristics and complications. Results Between July 2009 and March 2010, 94 PIAH (62% males) occurred in children <18 years of age, with a median age of 7 years (IQR: 3–12 years). Underlying diseases and predisposing factors were documented in 40 (43%) children; obesity (n = 12, 30%), asthma (n = 10, 25%) and neurologic disorders (n = 8, 20%) were most frequently reported. Sixteen (17%) children received oxygen supplementation; three (3%) children required mechanical ventilation. Six (6%) children were admitted to an intensive care unit, four of them with underlying chronic diseases. Conclusions Most PIAH demonstrated a benign course of disease. However, six children (6%) needed treatment at an intensive care unit for severe complications.